ADSORPTION OF PB(II) METAL IONS USING PVA-ALGINAT-PAPAYA SEEDS ADSORBENT - Haniifa Putri, Dhiya
Lead (Pb(II)) is a metal commonly found in industries such as battery production and automotive manufacturing. Wastewater containing heavy metals poses significant environmental risks and is highly toxic to human health. Therefore, separating Pb(II) metal ions from waste solutions before discharge into aquatic environments is crucial. Various recovery methods, including solvent extraction, ion exchange, filtration, and adsorption, are commonly used. Among these, adsorption is widely favored due to its simplicity, efficiency, cost-effectiveness, and the abundance of natural adsorbent materials. In this study, a PVA alginate-papaya seed (PAB) based adsorbent was synthesized to adsorb Pb(II) metal ions. Using papaya seeds can potentially increase the adsorption capacity because they contain cellulose and hemicellulose, which have abundant hydroxyl groups (-OH). The optimum adsorbent composition was obtained with a variation of the 1:1 ratio of alginate and papaya seeds. The adsorbent was characterized using Fourier Transform Infrared Spectroscopy (FTIR), the results were evidenced by a shift in wavelength values in certain groups, followed by Scanning Electron Microscopy (SEM)-Energy Dispersive Spectroscopy (EDS) with a Pb(II) content value of 2%. Adsorption using 0.05 g adsorbent reached optimum condition at pH 4 and contact time of 1440 min, with adsorption efficiency reaching 90%. The adsorption process followed a pseudo-second-order kinetics model with an experimental adsorption capacity (qm) of 22.4125 mg/g and a Langmuir adsorption isotherm model with an adsorption capacity (qmax) = 66 mg/g. Thermodynamic analysis showed that the adsorption was endothermic with ?H = 0.0146 kJ/mol, ?S = 1.1492 kJ/K mol, and the adsorption process was spontaneous. Repeated use of the adsorbent for 3 adsorption-desorption cycles with 0.1 M HNO3 desorption agent gave a good.